STATUS TERUMBU KARANG DAN IKAN KARANG DI GILI MATRA, NUSA TENGGARA BARAT - Ampou, Eghbert Elvan; Nugroho, Suciadi Catur; Widagti, Nuryani (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 14 No 1 (2020)DO - 10.24843/EJES.2020.v14.i01.p02, 2020)
This study aims to identify the status of reef fishes and coral reefs in Gili Meno, Air, and Trawangan or Gili Matra waters. This area is part of the North Lombok Regency, West Nusa Tenggara Province. Field observation was conducted on September 2011 at 11 (eleven) diving points. The video-transect method was used for observing the coral reef condition, while reef fishes abundance was observed by using visual-census method. The parameter that used to determine the condition of coral reef in study location are the percentage of live hard coral cover and index of coral mortality. In general, the result shows that percentage of live hard coral cover in each diving point ranged from 4.4% - 37.2% and the Coral Mortality Index (IMK) ranged form 0.40-0.92. The values describe that the condition of coral reef at eleven diving points vary from fair until poor condition. Current status of coral reef condition showed an insignificant increase from bad to moderate during the period 2011 -2018. There were 23 families of reef fishes from 46 genera were found during the study consisting of 16 genera of target fish groups, 5 genera of indicator fish group, and 25 genera of major fish group. The water quality is still within the limits of environmental quality standards.   Keywords: Reef fish, coral reef, Mortality Index, water quality, Gili Matra